Kemampuan Menyunting Teks Prosedur Kompleks Menggunakan Teknik Peer Editing Siswa Kelas X - Novita Nia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
This study aimed to determine the completeness of the ability to significantly edit complex procedural texts for class X MA Mazro'illah Lubuklinggau after the Peer Editing technique was applied. The research method is quasi-experimental. Data collection with test techniques. The data were analyzed using the T test formula. The results showed that the results of the hypothesis test were known to be 4.743. These results when consulted with tt (table with N-1 = 28-1 = 27 or db/df = 27) at a significance level of 1% that is 2.771 and a significance level of 5% is 2.052. This shows that the calculation results were greater than that at the 1% and 5% significance levels, or 4.743 > 2.771 and 4.743 > 2.052. The average student was greater than the KKM or 78.87 > 70 and the proportion of completeness reaches 89.29%. The results of the pretest students who completed were 9 people (32.14%), while the students who did not complete were 19 people (67.86%). Then, in the post-test results, 25 students (89.29%), while those who did not complete were 3 (10.71%). In conclusion, the application of Peer Editing techniques can significantly improve the ability to edit complex procedure texts for Class X MA Mazro'illah Lubuklinggau students. Keywords: Editing, Peer Editing Techniques, Complex Procedure Text